1980
DOI: 10.1038/284183a0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between coding sequences and function in haemoglobin

Abstract: Gilbert has suggested that the presence of intervening sequences in DNA, called introns, can speed evolution by allowing novel proteins to be constructed from the pieces of existing ones. This hypothesis further suggests that the coding sequences, called exons, correspond to functional parts of the protein. The most striking example so far is the case of the immunoglobulin gamma heavy chain, where the four polypeptide sequences corresponding to the four coding sequences form structurally and functionally disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…The analysis of hemoglobin functions showed that the amino acid residues associated with the heme contacts are concentrated in the central modules (M2 ϩ M3) as illustrated in Fig. 1 (6). In 1980, by using a protease, Craik et al (7,8) isolated the central region of the ␤-subunit, which corresponds to the module M2 ϩ M3 and is coded by the central exon of the ␤-subunit.…”
mentioning
confidence: 99%
“…The analysis of hemoglobin functions showed that the amino acid residues associated with the heme contacts are concentrated in the central modules (M2 ϩ M3) as illustrated in Fig. 1 (6). In 1980, by using a protease, Craik et al (7,8) isolated the central region of the ␤-subunit, which corresponds to the module M2 ϩ M3 and is coded by the central exon of the ␤-subunit.…”
mentioning
confidence: 99%
“…An original approach to investigate these fundamental aspects of protein structure and dynamics is to see if the domain encoded by the central exon of the myoglobin (Mb) gene, which consists of three exons and two long introns (3), behaves dynamically like the parent protein or if it displays peculiar properties. An answer to this question is also necessary to better understand why there are three exons in the genes encoding Mb and the hemoglobin (Hb) chains (4)(5)(6)(7).…”
Section: Tionmentioning
confidence: 99%
“…Given the similarity in the three-dimensional folding of Mb and Hb subunits (11) and in the exon-intron structure of the genes encoding for these proteins, 11 mini-Mb serves as a model ofgeneral validity. The central exons ofthe Mb and Hb chain genes code for the domain that provides the hydrophobic crevice where heme is bound, and the role proposed for the C-and N-terminal fragments is to optimize the fit between crevice and prosthetic group (6,7,12).…”
Section: Tionmentioning
confidence: 99%
“…They do, however, correspond to smaller, compact "modules" on the basis of a-carbon distance analysis (10). The central exon encodes a module that binds heme tightly and specifically but does not bind oxygen reversibly (11)(12)(13). A heme-binding peptide fragment (residues 32-139) of horse heart myoglobin encoded by the central exon and part of the third exon but totally lacking the first exon has been shown to bind both oxygen and carbon monoxide with rate constants similar to those in the native myoglobin (14).…”
mentioning
confidence: 99%